A Comparative Investigation of the Gel Chromatography Column Scanning Method for Quality Control of 99mTc-Methylenediphosphonate - Darte, L. (Nuklearmedizin - NuclearMedicine, 1981)
Gel chromatography column scanning (GCS) is the method of choice for quality control of 99mTc-MDP preparations. Using this method all the labelled components are obtained rapidly in one simple test procedure. The influence of various parameters such as gel type, column size, prehistory of column, equilibration, eluent, elution volume and flow rate upon the results have been investigated. Test results for 99mTc-MDP have been compared for several different GCS systems, a few TLC systems and column chromatography with fraction collection. The GCS technique, optimized for testing 99mTc-MDP preparations, has been applied in a few experiments in which very good reproducibility is required: Labelling kinetics and stability when stored at room temperature or in a refrigerator and influence of the 99mTc/(99mTc + 99Tc) atomic ratio and of the amount of radioactivity on the 99mTc-MDP labelling yield, covering parameter ranges of clinical interest, have been studied.